An image processing application for quantification of protein ag-gregates in Caenorhabditis elegans - Castro, Andreia Cristiana Teixeira de (2011)
Protein aggregation became a widely accepted marker of many polyQ disorders, including Machado-Joseph disease (MJD), and is often used as readout for disease progression and development of therapeutic strategies. The lack of good platforms to rapidly quantify protein aggregates in a wide range of disease animal models prompted us to generate a novel image processing application that automatically identifies and quantifies the aggregates in a standardized and operator-independent manner. We propose here a novel image processing tool to quantify the protein aggregates in a Caenorhabditis elegans (C. elegans) model of MJD. Confocal microscopy images were obtained from animals of different genetic conditions. The image processing application was developed using MeVisLab as a platform to process, analyse and visualize the images obtained from those animals. All segmentation algorithms were based on intensity pixel levels.The quantification of area or numbers of aggregates per total body area, as well as the number of aggregates per animal were shown to be reliable and reproducible measures of protein aggregation in C. elegans. The results obtained were consistent with the levels of aggregation observed in the images. In conclusion, this novel imaging processing application allows the non-biased, reliable and high throughput quantification of protein aggregates in a C. elegans model of MJD, which may contribute to a significant improvement on the prognosis of treatment effectiveness for this group of disorders.